2020
DOI: 10.31703/glr.2020(v-ii).14
|View full text |Cite
|
Sign up to set email alerts
|

Brain Based Learning and Urdu EFL Learners' Academic Achievement in English at Secondary School Level in District Vehari

Abstract: Current educational standards are changing dramatically to meet student's academic needs, and learners are at the heart of the educational system. The sole objective of the study is to compare the effect of brain-based learning teaching method and traditional teaching method on students' academic achievement in English at the secondary school level. For this study, the researcher has selected a convenient sample of sixty students enrolled in GBHS9-11/WB who took part in the experiment, and these were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
1
3
0
Order By: Relevance
“…The results of the present research were in line with the results of Kohar (2020,2022), Nur, Hasyim, and Khalikin (2020), Ali et al (2020), Yunita (2020), Bedeer (2018), Syahbandi (2018), andShabatat andAl-Tarawneh (2016), as they all proved the positive effect of using brain-based learning strategy in developing English reading comprehension skills. The results were revealed:…”
Section: Results Related To the Second Hypothesissupporting
confidence: 90%
“…The results of the present research were in line with the results of Kohar (2020,2022), Nur, Hasyim, and Khalikin (2020), Ali et al (2020), Yunita (2020), Bedeer (2018), Syahbandi (2018), andShabatat andAl-Tarawneh (2016), as they all proved the positive effect of using brain-based learning strategy in developing English reading comprehension skills. The results were revealed:…”
Section: Results Related To the Second Hypothesissupporting
confidence: 90%
“…This learning approach emphasises how the brains acquire learning (Erişti & Akdeniz, 2016), acquire insights (Ofen et al, 2016), and develop in an educational environment (Davidesco et al, 2021). By participating in interactive conversations (Khalil et al, 2019), the learners actively deepen their comprehension of the problem throughout this learning process (Ali et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The BBL teaching approach helps pupils learn from personal experiences and develop insightful ideas (Al-Balushi & Al-Balushi, 2018). It not only raises pupils' academic achievement but also fosters cooperation, teamwork, and dedication (Duncan, 2020), which enables pupils to draw lessons from their experiences in life, which is advantageous to both educators and pupils (Ali et al, 2020). The literature also found that the BBL approach perceives learning as a means that requires engagement and fosters creativity through obstacles (Cheung et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is a way of teaching that, instead of long lectures given by the teacher, stresses physical movement, student-to-student instruction, and group work. Neuroplasticity, the process by which the brain's connections are reorganized in reaction to new knowledge, is fundamental to brain-based learning (Ali, Kashif, & Shahzad, 2020). The objective of the study is to explore secondary school teachers' perceptions of the effectiveness of brainbased learning strategies for English learning in the classroom.…”
mentioning
confidence: 99%